Diabetes Confers Little to No Increased Risk of Postoperative Complications After Hip Fracture Surgery in Geriatric Patients. Issue 3 (March 2015) - Golinvaux, Nicholas S.; Bohl, Daniel D.; Basques, Bryce A.; Baumgaertner, Michael R.; Grauer, Jonathan N.
Abstract: Background: Diabetes and hip fractures in geriatric patients are common, and many elderly patients have a history of diabetes. However, the influence of diabetes on surgical complications may vary based on which particular type of diabetes a patient has. To our knowledge, no prior study has stratified patients with diabetes to compare patients with noninsulin‐dependent and insulin‐dependent diabetes regarding rates of postoperative adverse events, length of hospitalization, and readmission rate after surgical stabilization of hip fractures in geriatric patients. Questions/purposes: We asked whether patients with noninsulin‐dependent or insulin‐dependent diabetes are at increased risk (1) of sustaining an aggregated serious adverse event, aggregated minor adverse event, extended length of stay, or hospital readmission within 30 days of hip fracture surgery; (2) of experiencing any individual serious adverse event within 30 days of hip fracture surgery; and (3) of experiencing any individual minor adverse event within 30 days of hip fracture surgery. Methods: Patients older than 65 years undergoing surgery for hip fracture between 2005 and 2012 were identified (n = 9938) from the American College of Surgeons National Surgical Quality Improvement Program ® database. This database reports events within 30 days of the surgery. Demographics were compared between three groups of patients: patients with noninsulin‐dependent diabetes, patients with insulin‐dependent diabetes, and patients without diabetes. Patients without diabetes served as the reference group, and the relative risks for aggregated serious adverse events, aggregated minor adverse events, length of stay greater than 9 days, and readmission within 30 days were calculated for patients with noninsulin‐dependent and with insulin‐dependent diabetes. We then calculated relative risks for each specific serious adverse event and minor adverse event using multivariate analyses. Results: Patients with noninsulin‐dependent and insulin‐dependent diabetes were at no greater risk of sustaining an aggregated serious adverse event, aggregated minor adverse event, extended postoperative length of stay, or readmission. Among individual serious adverse events, only postoperative myocardial infarction was found to be increased in the diabetic groups (relative risk [RR] = 1.9 for noninsulin‐dependent diabetes, 95% CI, 1.3‐2.8; RR = 1.5 for insulin‐dependent diabetes, CI, 0.9‐2.6; p = 0.003). Patients with noninsulin‐dependent and insulin‐dependent diabetes were at no greater risk of sustaining any individual minor adverse event. Conclusions: Despite previously reported and perceived risks associated with diabetes, we found little difference in terms of perioperative risk among geriatric patients with hip fracture with noninsulin‐dependent or insulin‐dependent diabetes relative to patients without diabetes. Clinically, the implications of these findings will help to improve, specify, and increase the efficiency of the preoperative workup and counseling of patients with diabetes who need hip fracture surgery. Level of Evidence: Level III, case‐control study. See Instructions for Authors for a complete description of levels of evidence.